2006
DOI: 10.1111/j.1439-0442.2006.00886.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex Steroids Level in Blood Plasma and Ovarian Follicles of the Chimeric Chicken

Abstract: The study was performed to determine the hormonal status of mature germline chimeras obtained by blastodermal cell transfer from chicken embryos of a donor breed [Green-legged Partridgelike breed (GP) x Araucana (AR)] to those of a recipient breed [White Leghorn (WL)] being at the same stage of embryonic development. The egg-laying chimeras and WL hens (control) of the same age were used in the experiment. At first, blood samples were taken from each bird at 0.5, 5, 12.5 and 18.5 h following oviposition. Subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
(61 reference statements)
1
11
0
Order By: Relevance
“…These results were in agreement with expectations, especially the high rate of gonad chimerism observed in progeny tested chimeras produced using the same method (BEDNARCZYK et al 2002;SECHMAN et al 2006). Gonads are the final destination for PG.…”
Section: Discussionsupporting
confidence: 92%
“…These results were in agreement with expectations, especially the high rate of gonad chimerism observed in progeny tested chimeras produced using the same method (BEDNARCZYK et al 2002;SECHMAN et al 2006). Gonads are the final destination for PG.…”
Section: Discussionsupporting
confidence: 92%
“…The wall of the ovarian follicle consists of concentric layers of tissue that surround the oocyte and yolk, including the granulosa and the theca (interna and externa) (Johnson, 2000). The granulosa layer produces predominantly progesterone (P4) which is a precursor for testosterone (T) and oestradiol (E2) synthesis by the theca interna and externa layers, respectively (Bahr et al, 1983;Nitta et al, 1991;Rząsa et al, 2002;Sechman et al, 2004bSechman et al, , 2006. The stromal tissue with cortical follicles below 1 mm and the theca layer of white nonhierarchical follicles (< 8 mm), via the Δ 5 steroidogenic pathway, produce mainly T which is immediately converted to E2 by aromatase P450 (P450arom) (Lee et al, 1998).…”
mentioning
confidence: 99%
“…The liver (Liv) was used as a negative control; nd -not detected: a, b -significant at P#0.05. (BAHR et al 1983;ROBINSON & ETCHES 1986;GOMEZ et al 1998;LEE et al 1998;PROSZKO-WIEC-WÊGLARZ et al 2005;RZ¥SA et al 2009;SECHMAN et al 2006;SECHMAN et al 2009). Histochemical and immunohistochemical studies have also confirmed that granulosa cells of preovulatory follicles show 3â-HSD activity, which means that they are a site of steroid biosynthesis (ARMSTRONG 1979;DAVIDSON et al 1979;MARRONE & SEBRING 1989;NITTA et al 1993).…”
Section: Resultsmentioning
confidence: 97%
“…The structure and function of granulosa cells from preovulatory ovarian follicles, which are the principal source of progesterone (P 4 ) in avian ovaries, and their role in ovarian follicle growth has been the subject of several studies (ARMSTRONG 1979;BAHR et al 1983;GOMEZ et al 1998;NITTA et al 1993;YOSHIMURA et al 1993;YAO & BAHR 2001a;PROSZKOWIEC-WÊGLARZ et al 2005;RZ¥SA et al 2009;SECHMAN et al 2006;SECHMAN et al 2009). Most of these studies regarded the granulosa layer as a uniform structure.…”
mentioning
confidence: 99%